Perception regarding COVID-19 vaccine and COVID appropriate behavior among adolescents at a tertiary hospital, West Bengal: A longitudinal survey - Ruby Dhankher; Ananya Mukhopadhyay; Saswati Bhowmick; Latha Thimmappa; Ritesh Singh; Poonam Joshi; Jamuna Rani (Elsevier, 2023)
Background: Vaccination against COVID 19 and observing COVID appropriate behavior are effective measures to control, manage and prevent COVID-19 infection. With India starting its adolescent vaccination program, this study aimed to explore the adolescents' perception of vaccination, their COVID-appropriate behavior, compliance with two doses of COVID-19 vaccines and the experienced side effects following vaccination. Methods: A longitudinal survey was conducted among 440 adolescents visiting the COVID Vaccination Center (CVC) of a tertiary hospital in West Bengal. In the survey, adolescents were asked about family socio-demographic characteristics, their opinions on COVID-19 vaccines, and COVID-19 Appropriate Behavior (CAB) practices. Voluntary participants were given a questionnaire to fill and a telephonic interview was taken regarding side effects experienced following the vaccination and their compliance to both doses of vaccine. Results: The majority of adolescents (99.3%) had taken vaccines by their own wish. The reason for willingness to take the vaccine was the fear of being infected with COVID-19 infection (50.5%). Maximum adolescents got information regarding the COVID vaccination program through the internet (41.8%) followed by family members (30.5%). The majority of adolescents (70.9%) had a good perception of COVID-19 vaccination. A significant number of adolescents (44.8%) strongly disagreed with the statement that they don't need to follow COVID appropriate behavior after vaccination. Conclusion: The majority of adolescents had a good perception regarding COVID-19.